Effect of Salivary pH on Water Absorption and Solubility of Enhanced Resin- Modified Glass Ionomer - Eriwati, Yosi Kusuma; Dhiaulfikri, Muhammad; Herda, Ellyza (Journal of Dentistry Indonesia, 2020)
The influence of immersion period and liquid pH on water absorption capacity and solubility of the resin-modified glass ionomer cement (RMGIC) raises the question of whether the critical pH of hydroxyapatite and fluoroapatite influences the water absorption capacity and solubility of enhanced resin-modified glass ionomer (ERMGI). Objective: This study was designed to investigate the effects of immersion periods and various pH levels of artificial saliva on the water absorption and solubility of RMGIC and ERMGI. Methods: Fifty-four disc-shaped specimens (15 mm x 1 mm) of enhanced RMGI (ACTIVATM BioACTIVE-RESTORATIVE, Pulpdent, Watertown, MA, USA) and 54 disc-shaped specimens (15 mm x 1 mm) of RMGIC (Fuji II LC Capsules, GC Corp, Tokyo, Japan) were prepared. Both materials were divided into 9 groups based on artificial saliva pH (pH 7, pH 5.5, and pH 4.5) and immersion time (1, 7, and 14 days). Water absorption and solubility were measured based on ISO 4049: 2009. Data were analyzed statistically using one-way ANOVA. Results: The results showed significant differences in water absorption and solubility value between RMGIC and enhanced RMGI for all the groups. Both materials showed increased water absorption and solubility when immersed in artificial saliva that exhibited a lower pH level and under higher immersion period. Conclusion: Lower pH levels and longer immersion time influence the water absorption and solubility of enhanced RMGI and RMGIC.